1983
DOI: 10.1002/bjs.1800701009
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic metastases—a physiological approach to treatment

Abstract: Hepatic metastases derived from primary malignancy of the gastrointestinal tract have a grave prognosis, with median survival rates varying from 3 to 11 months. Surgery for isolated metastases and intrahepatic artery chemotherapy are the most effective treatment options currently available. We have explored the potential use of radioactive microspheres delivered into the liver by the hepatic artery as a form of internally irradiating metastatic liver cancer. Microspheres containing radioactive Yttrium injected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Finally, medical therapy used solely for symptom control also has survival rates of 76% and 39% at 1 and 3 years from initiation of therapy respectively. 6 Palliative embolization therapies have yielded mixed results. Studies of TAE using polyvinyl alcohol particles or gelfoam report survival rates of 60% to 94% (1 year) and 14% to 51% (5 year).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, medical therapy used solely for symptom control also has survival rates of 76% and 39% at 1 and 3 years from initiation of therapy respectively. 6 Palliative embolization therapies have yielded mixed results. Studies of TAE using polyvinyl alcohol particles or gelfoam report survival rates of 60% to 94% (1 year) and 14% to 51% (5 year).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, Ն90% of patients present with multiple hepatic metastatic lesions excluding them from surgical cure. 4,5 Therapies for unresectable metastatic NET include (a) medical (eg, somatostatin analogues) 6 ; (b) ablative such as cryotherapy 7 or radiofrequency ablation (RFA) 8,9 ; (c) systemic chemotherapy, 10 and; (d) transcatheter arterial embolization (TAE) or chemoembolization (TACE). 4,11,12 These therapies have been effective at improving patient symptomatology but lack robust clinical trial data, long-term survival Ͼ5 years (cryotherapy, RFA, or medical therapy), or have 5-year survival percentages widely ranging from 14% to 60% (TAE/TACE).…”
mentioning
confidence: 99%
“…The SIR-Spheres are embolised into the hepatic artery and result in high doses of radiation being selectively targeted to tumours, regardless of their number or position within the liver. The technique of SIRT, dosimetry, and preclinical studies have all been previously reported [2][3][4][5][6][7]. Injection of specific vasoactive drugs into the hepatic arterial circulation has been shown to greatly enhance tumour targeting with SIR-Spheres [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Microspheres of 30-40 tm (range 10-90 jLm) in diameter should lodge in the hepatic-arterial microvasculature when injected into the common hepatic artery. Chamberlain and Gray (1983) demonstrated that in rabbit VX2 liver tumours, the concentration of microspheres was 30-fold higher than in the normal liver tissues. Therefore in hypervascular regions of tumours the aterial capillary obstruction and the slowdown of blood flow rate result in the entrapment of a greater volume of drug solution than in normal liver.…”
Section: Discussionmentioning
confidence: 96%